2015
DOI: 10.1007/s11356-015-4573-9
|View full text |Cite
|
Sign up to set email alerts
|

Functions of slags and gravels as substrates in large-scale demonstration constructed wetland systems for polluted river water treatment

Abstract: The choice of substrates with high adsorption capacity, yet readily available and economical is vital for sustainable pollutants removal in constructed wetlands (CWs). Two identical large-scale demonstration horizontal subsurface flow (HSSF) CWs (surface area, 340 m(2); depth, 0.6 m; HLR, 0.2 m/day) with gravel or slag substrates were evaluated for their potential use in remediating polluted urban river water in the prevailing climate of northwest China. Batch experiments to elucidate phosphorus adsorption mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…Wetland media could be sand, gravel, rock, or organic material such as soil and compost, which provide the primary support for the wetland plants and microorganism growth, enhancing biodegradation of wastewater pollutants in addition to its impact on system hydrology mechanisms (Tietz et al 2007 ; Meng et al 2014 ). Moreover, wetland substrates remove contaminants from the wastewater by ion exchange, adsorption, precipitation, and complexation (Dordio and Carvalho 2013 ; Ge et al 2015 ), enhancing the effluent quality to meet reuse standards in agriculture. However, the chemical composition of wetland substrate can affect the system efficiency.…”
Section: Sustainable Design and Operation Of Constructed Wetlandsmentioning
confidence: 99%
“…Wetland media could be sand, gravel, rock, or organic material such as soil and compost, which provide the primary support for the wetland plants and microorganism growth, enhancing biodegradation of wastewater pollutants in addition to its impact on system hydrology mechanisms (Tietz et al 2007 ; Meng et al 2014 ). Moreover, wetland substrates remove contaminants from the wastewater by ion exchange, adsorption, precipitation, and complexation (Dordio and Carvalho 2013 ; Ge et al 2015 ), enhancing the effluent quality to meet reuse standards in agriculture. However, the chemical composition of wetland substrate can affect the system efficiency.…”
Section: Sustainable Design and Operation Of Constructed Wetlandsmentioning
confidence: 99%
“…However, the only sustainable mechanism for TP removal is plant uptake and subsequent harvesting. It has been accepted traditionally that the amount of P that can be abated by harvesting constitutes only an insignificant fraction of the amount of the P load in the system [58], but recently it has been demonstrated that a well-developed Phragmites australis can assimilate up to 75.1% of total dissolved P influent [14].…”
Section: Surface System Optimizationmentioning
confidence: 99%
“…When P abatement is required, it is necessary to incorporate an alternative treatment. Different alternatives like the use of slags, which have been studied recently, remove P mainly via CaO-slag dissolution followed by Ca 2+ phosphate precipitation [14] or the use of an "irregularly shaped" HF-CW as described by Gorra et al [65].…”
Section: Surface Optimization Considering Tpmentioning
confidence: 99%
“…Adsorption has been shown to be an important removal mechanism for antiscalants and corrosion inhibitors. The CW substrate composition defines the adsorption capacity of the CW (Ge et al, 2015;Sakadevan & Bavor, 1998). recently published an overview of commonly used substrates to enhance adsorption processes in CWs, such as natural clay minerals, industrial by-products and activated carbon.…”
Section: Cw Design Considerationsmentioning
confidence: 99%